Innovative Approaches in Upper-Limb Stroke Rehabilitation: A Systematic Review of Emerging Therapies and Technologies - Dr Anubha Aranake; Dr. Suraj B. Kanase (The Bioscan, 2025)
Background: Stroke is a leading cause of disability, often resulting in upper limb motor impairments that significantly affect patients’ quality of life Various physiotherapy interventions, including neurostimulation, robotic-assisted therapy, mirror therapy, task-specific training, and sensory interventions, have been explored to enhance motor recovery and reduce spasticity. Objective: This systematic review aims to evaluate the effectiveness of diverse upper-limb rehabilitation strategies in stroke patients by analyzing outcomes related to motor function, spasticity, and activities of daily living (ADLs). Methods: A total of 15 randomized controlled trials (RCTs) published between 2013 and 2022 were included in this review. The studies involved varying sample sizes and employed different rehabilitation approaches. The primary outcome measures assessed included motor performance, spasticity reduction, functional mobility, and quality of life improvements. Results: The findings revealed that physiotherapy interventions significantly improved motor function and reduced spasticity in stroke patients. Neurostimulation techniques, such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS), demonstrated positive effects on spasticity and functional recovery. Robotic-assisted and virtual reality-based therapies enhanced motor skills and ADLs. Mirror therapy and sensory interventions promoted sensorimotor integration and improved coordination. Conclusion: The review highlights the efficacy of various physiotherapy interventions in enhancing upper-limb motor recovery and reducing stroke-related disability. Combined or hybrid approaches, such as robotic-assisted therapy with task-specific training, showed promising results. Future research should focus on larger-scale trials and long-term follow-ups to validate these findings and optimize rehabilitation protocols.